2016
DOI: 10.14260/jemds/2016/258
|View full text |Cite
|
Sign up to set email alerts
|

Role of Red Blood Cell Distribution Width as a Prognostic Marker in Patients With Severe Sepsis and Septic Shock

Abstract: BACKGROUNDRed Cell Distribution Width (RDW) is widely available to clinicians, because it is routinely reported as part of complete blood count. Several studies have reported that RDW is closely related to outcome in critically ill patients. Severe sepsis and septic shock are increasing in incidence and contributing significantly to mortality. Prediction of outcome for patients with sepsis using easily available and reliable marker may facilitate more aggressive interventions made at appropriate time. We studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…RDW showed significant association with mortality on admission and day 3. In agreement, Punekar et al [29] reported that baseline RDW and 72 h later were linked to sepsis outcome. Lorente et al [30] found higher RDW in non-survivors on first day and 72 h later.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…RDW showed significant association with mortality on admission and day 3. In agreement, Punekar et al [29] reported that baseline RDW and 72 h later were linked to sepsis outcome. Lorente et al [30] found higher RDW in non-survivors on first day and 72 h later.…”
Section: Discussionsupporting
confidence: 65%
“…During sepsis, various pathophysiological mechanisms affect RDW, such as oxidative stress, proinflammatory cytokines, systemic inflammatory response, and renal dysfunction [29]. RDW showed significant association with mortality on admission and day 3.…”
Section: Discussionmentioning
confidence: 95%